Effects of topical capsaicin in seasonal allergic rhinitis. Issue 3 (March 1995) - Greiff, L; Svensson, C; Andersson, M; Persson, C G
Abstract : BACKGROUND--Mucosal exudation (luminal entry) of bulk plasma is a key feature of airway defence and inflammation. In guinea pig and rat airways this response is readily produced by neurogenic irritants, notably capsaicin. Thus "neurogenic airway inflammation" has become an established concept. The present study examines whether capsaicin also produces mucosal exudation of plasma in human nasal airways both in health and disease (seasonal allergic rhinitis). METHODS--Pain-producing concentrations of capsaicin (30-300 ng/ml) were applied to the nasal mucosal surface both before and late into the pollen season. Levels of albumin in nasal lavage fluid were measured as an index of mucosal exudation of plasma. In a separate group of patients with seasonal allergic rhinitis nasal challenge with an exudative concentration of histamine was carried out before the birch pollen season and concentrations of albumin in lavage fluid were measured. RESULTS--Pollen counts and symptom scores revealed a mild pollen season. Capsaicin produced considerable nasal pain and this response was augmented late into the season when capsaicin also produced nasal blockage. However, capsaicin failed to produce any mucosal exudation of plasma either before or late into the pollen season. The exudative effect of histamine was confirmed. CONCLUSIONS--The augmented pain response to capsaicin suggests that a sensory nerve hyperresponsiveness may characterise allergic airways disease. In contrast to the effects on animal airways, capsaicin failed to produce mucosal exudation of plasma in the human nasal airway. The animal based neurogenic inflammation concept is therefore not valid for the human nasal airway, not even in inflamed airways when a neural hyperresponsiveness has developed.